(untitled) (Journal of Engineering Science, 2020)
In this study, the ZnO nanoparticles solution was directly applied on to the 100% cotton knit & woven fabric to impart antibacterial property using both spin coater & pad-dry-cure method. Then, the disc diffusion method was used to assess the antibacterial activity of the finished fabrics. The topographical analysis of untreated, treated, and washed fabrics of different structures (knit and woven) were studied and compared. The results showed that the finished fabric demonstrated significant antibacterial activity against S. aureus and E. coli. As per result, it was also found that double jersey (rib) fabric showed highest amount of bacterial protection & pad-dry-cure method showed better result against bacterial attack than spin coating method. Moreover, gram negative bacteria (E. coli) showed more strength against antibacterial treated unwashed and washed fabrics than gram positive bacteria (S. aureus). Journal of Engineering Science 11(1), 2020, 61-65